Incidental nodal metastasis of differentiated thyroid carcinoma in neck dissection specimens from head and neck cancer patients. Issue 4 (28th February 2017) - Lenzi, R; Marchetti, M; Muscatello, L
Abstract: Background: Occult differentiated thyroid carcinomas are not uncommon. The initial presentation of a thyroid carcinoma is often detection of a metastatic cervical lymph node. Methods: A retrospective review was performed of the medical records of 304 patients who underwent neck dissection between 1996 and 2008 for squamous cell carcinoma of the head and neck. Results: Ten patients (3.3 per cent) had nodal metastasis originating from papillary thyroid cancer. All of these patients underwent thyroidectomy and post-operative 131 iodine radiometabolic therapy. No patient developed a thyroid tumour after surgery. Conclusion: Despite its metastatic spread, thyroid cancer does not affect the overall prognosis of patients who are already being treated for a more aggressive malignancy. However, in otherwise healthy patients, it is worth treating this second malignancy to avoid potential complications related to local disease or metastatic thyroid cancer.